Enhanced Growth Performance and Salinity Tolerance in Transgenic Switchgrass via Overexpressing Vacuolar Na+ (K+)/H+ Antiporter Gene (PvNHX1) - Huang, Yanhua; Guan, Cong; Liu, Yanrong; Chen, Baoyue; Yuan, Shan; Cui, Xin; Zhang, Yunwei; Yang, Fuyu (Frontiers in Plant Science, 2017)
Switchgrass (Panicum virgatum L.) has been increasingly recognized as one of the most valuable perennial bioenergy crop. Genetic engineering approaches aim to improve biomass production of switchgrass, especially under abiotic stresses. Plant vacuolar Na+/H+ antiporters (NHXs) play important roles in response to salt stress by compartmentalizing excess cytosolic Na+ into vacuoles and maintaining cellular homeostasis and ionic equilibrium. In the present study, a vacuolar Na+/H+ antiporter gene in switchgrass was isolated and its expression patterns in various tissues and different development stages were determined as well. The full-length NHX1 gene, designated PvNHX1 (GenBank accession no. KJ739865), was 1699-bp in length with an opening reading frame (ORF) of 1611 nucleotides encoding a 536-amino acid protein. The PvNHX1 was detected in almost all switchgrass development stage and tissues, and exhibited relatively higher levels in the R2 stage and in the leaf, respectively. We generated transgenic switchgrass by Agrobacterium-mediated transformation. Transgenic switchgrass showed obvious advantages with respect to plant height, leaf width, leaf length and flowering compared to the wild-type (WT) and transgenic control (EV, expressing the empty vector only) plants, suggesting PvNHX1 may serve as a promoter in switchgrass growth and flowering. Furthermore, transgenic switchgrass performed better in both growth-related phenotypes and physiological capacities (higher proline and relative water contents, lower electrolyte leakage and malonaldehyde etc.) than those of control plants under high salinity stress. Taken together, studies on transgenic switchgrass overexpressing PvNHX1 reveals the critical functions of vacuolar Na+/H+ antiporters in prompting plant growth, flowering and salt tolerance. Our data will provide a valuable foundation for further researches on the potential roles of NHXs in plants.